SISTEM PRESENSI MENGGUNAKAN QR CODE DAN GOOGLE SPREDSHEET DI SEKOLAH MADRASAH IPTIDAIYAH DI DESA TREBUNGAN - Nur Azizah; Raudatul Jannah; Rudi Agus Wilantara; Andika Fajri; Muhammad Rifqi A.H (Jurnal Masyarakat Berdikari dan Berkarya (Mardika), 2024)
Education is one of the important aspects in the development of a nation. Along with the development of technology, many educational institutions, including Madrasah Ibtidaiyah schools in Trebungan Village, are required to utilize technology to improve the efficiency and effectiveness of managing activities, including the student attendance process. The methods used include the observation method, namely the method by making direct observations on the object to be observed. The manual attendance system that is still widely used in schools today often causes various problems, such as data inaccuracy, loss of attendance sheets, and time-consuming data processing.To overcome these problems, innovation is needed in student attendance management. Therefore, a student attendance application was designed and implemented for schools, and in the design to implementation stage Digital Attendance has been able to run well. With this application, it can prevent attendance fraud, because attendance is stored in the form of an excel file and can be automatically stored in an excel file (google spreadsheet).